2019
DOI: 10.3892/etm.2019.7939
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates brain injury via the TGF‑β‑mediated ERK signaling pathway in a rat model of cerebral hemorrhage

Abstract: Brain injury is the most common intracranial injury in human cerebrovascular disease, which may lead to ischemic stroke. Resveratrol induces ameliorative effects in the treatment of certain human diseases by regulating different signaling pathways. The present study assessed the therapeutic effects of resveratrol and its potential mechanism of action in the neurons from rats with ischemia/reperfusion-induced cerebral hemorrhage. The rat model of cerebral hemorrhage was established and reverse transcription-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Although resveratrol had demonstrated to possess significant protective effects against I/R injury of various organs, including kidney [12][13][14][15][16][17][18] , we demonstrated for the first time the protective effects of resveratrol in diabetic rats after renal I/R injury. Our study showed that administration of resveratrol proved to be an effective treatment against renal I/R in diabetic rats.…”
Section: ■ Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although resveratrol had demonstrated to possess significant protective effects against I/R injury of various organs, including kidney [12][13][14][15][16][17][18] , we demonstrated for the first time the protective effects of resveratrol in diabetic rats after renal I/R injury. Our study showed that administration of resveratrol proved to be an effective treatment against renal I/R in diabetic rats.…”
Section: ■ Discussionmentioning
confidence: 76%
“…Resveratrol was a polyphenol, which has been reported to possess a kind of pharmacological effects, such as anti-inflammatory properties, protection against coronary heart disease, modulation of lipid metabolism and prevention of cancer [9][10][11] . Resveratrol has significant protective effects against I/R injury in various organs [12][13][14][15][16] . Specifically, resveratrol has shown to protect against several types of renal injury by inhibiting oxidative stress and ameliorating inflammatory response, including diabetic nephropathy, drug-induced injury, and I/R injury [17][18] .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, the administration of Res was found to improve the blood–brain barrier (BBB) and inhibit apoptosis in neuronal cells. These protective effects of Res were found to be mediated via the inhibition of TGF-β-mediated ERK [ 200 ]. Moreover, it was found that exposing rats to alcohol is associated with an increase in levels of cytokines such as TGF-β.…”
Section: Resveratrol and Tgf-β Signaling Pathwaymentioning
confidence: 99%
“…Also, it diminishes the levels of oxidative stress and inflammatory factors as well as inhibits apoptosis in neuronal cells (Z. Dou, Rong, Zhao, Zhang, & Lv, 2019; Lin et al, 2020; Y.‐K. Xie, Zhou, et al, 2019; L. Zhang, Wang, et al, 2019; R. Zhao, Zhao, Su, Zhang, & Zhao, 2019).…”
Section: Neuroprotective Activity Of Resveratrolmentioning
confidence: 99%
“…This naturally occurring compound is ableto affect signaling pathways to exert its neuroprotective activity. Also, it diminishes the levels of oxidative stress and inflammatory factors as well as inhibits apoptosis in neuronal cells (Z Dou, Rong, Zhao, Zhang, & Lv, 2019;Lin et al, 2020;Y.-K. Xie, Zhou, et al, 2019;R. Zhao, Zhao, Su, Zhang, & Zhao, 2019)…”
mentioning
confidence: 99%